Efektivitas Penilaian Dinamis Berbantuan Google Form dalam Pembelajaran Membaca Teks Deskripsi - Astuti Astuti; Ida Nuraeni; Ulfah Ulfah; Syamsuddin Syamsuddin; Sukma Sukma (Aksara, 2025)
This study aims to test the effectiveness of dynamic assessment assisted by Google Forms in learning to read descriptive texts for seventh-grade students. The research method used is a quasi-experimental design with a nonequivalent control group design. The research population consists of all seventh-grade students of SMPN 1 Wita Ponda, totaling 150 students, with a research sample of 66 students divided into 33 students in the experimental class and 33 students in the control class, selected using simple random sampling. Data collection techniques used a multiple-choice test consisting of 25 questions given in the pretest and posttest. Data analysis techniques used descriptive statistics and inferential statistics using t-test assisted by SPSS version 30. The results of the study showed that the experimental group experienced an increase in the average score from 70.58 in the pretest to 83.27 in the posttest, while the control group only increased from 65.03 to 72.30. The normality test in the experimental class obtained an index of 0.180>0.05 and in the control class obtained 0.131>0.05, therefore the data is normally distributed. The homogeneity of variance test on the posttest scores of the control class and the experimental class obtained a p-value of 0.680, where p is greater than 0.05, thus it is declared homogeneous. The hypothesis test results using inferential statistics stated that the research hypothesis was accepted because the p-value (2 tailed) was <0.001 and the t-count > t-table value (7.323 > 2.650), so it can be concluded that the hypothesis in this study is accepted. The research results prove that dynamic assessment assisted by Google Forms is effective in learning to read descriptive texts. AbstrakPenelitian ini bertujuan untuk menguji efektivitas penilaian dinamis berbantuan Google Form dalam pembelajaran membaca teks deskripsi pada siswa kelas VII. Metode penelitian yang digunakan adalah quasi-experimental design dengan desain nonequivalent control group. Populasi penelitian adalah seluruh siswa kelas VII SMPN 1 Wita Ponda sebanyak 150 siswa, dengan sampel penelitian sebanyak 66 siswa yang terbagi menjadi 33 siswa kelas eksperimen dan 33 siswa kelas kontrol yang dipilih menggunakan teknik simple random sampling. Teknik pengumpulan data menggunakan tes pilihan ganda sebanyak 25 butir soal yang diberikan pada pretest dan posttest. Teknik analisis data menggunakan statistik deskriptif dan statistik inferensial uji-t dengan bantuan SPSS versi 30. Hasil penelitian menunjukkan bahwa kelompok eksperimen mengalami peningkatan nilai rata-rata dari 70,58 pada pretest menjadi 83,27 pada posttest, sedangkan kelompok kontrol hanya meningkat dari 65,03 menjadi 72,30. Uji normalitas pada kelas eksperimen diperoleh indeks sebesar 0,180>0,05 dan kelas kontrol diperoleh 0,131>0,05, maka data berdistribusi normal. Hasil uji homogenitas variansi dari nilai posttest kelas kontrol dan kelas eksperimen diperoleh nilai p=0,680 dimana p lebih besar dari 0,05 sehingga dinyatakan homogen. Hasil uji hipotesis dengan statistik inferensial dinyatakan bahwa hipotesis penelitian diterima karena p-value (2 tailed) adalah <0,001 dan nilai thitung>nilai ttabel (7,323 > 2,650), sehingga dapat ditarik kesimpulan bahwa hipotesis dalam penelitian ini diterima. Hasil penelitian membuktikan bahwa penilaian dinamis berbantuan google form efektif dalam pembelajaran membaca teks deskripsi.